(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The equilibrium structure, spectroscopy constants and anharmonic force field of PO^-_2 anion have been investigated at MP2, B3LYP, B3P86, B3PW91 methods employing three basis sets, 6-311++G(2d,2p), 6-311++G(3df,3pd) and cc-pVQZ, respectively. The computed geometries, rotational constants, vibration-rotation interaction constants, quartic centrifugal distortion constants, and coriolis coupling constants of PO^-_2 are compared with the available experimental or theoretical data. The fundamental frequencies, rotational constants of ground state, sextic centrifugal distortion constants, cubic and quartic force constants of PO^-_2 are firstly predicted. The calculated results show that the B3P86/6-311++G(3df, 3pd) results are in excellent agreement with experiment and represent a substantial improvement over the results obtained from MP2. The other DFTmethods are also advisable choices to study the anharmonic force field of PO^-_2. The predicted spectroscopic constants may provide the useful data for the experiment studies of the corresponding spectroscopic constants of PO^-_2.